2017
DOI: 10.5194/isprs-archives-xlii-3-w3-123-2017
|View full text |Cite
|
Sign up to set email alerts
|

Time Series of Images to Improve Tree Species Classification

Abstract: ABSTRACT:Tree species classification provides valuable information to forest monitoring and management. The high floristic variation of the tree species appears as a challenging issue in the tree species classification because the vegetation characteristics changes according to the season. To help to monitor this complex environment, the imaging spectroscopy has been largely applied since the development of miniaturized sensors attached to Unmanned Aerial Vehicles (UAV). Considering the seasonal changes in for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Hill et al (2010) had reported that the ability to discriminate and map temperate deciduous tree species in airborne multispectral imagery increased using timeseries data: from kappa 0.67 for a single image to kappa 0.85 for three images combined (one from autumn, one from the green-up, and one from full-leaf phase). Miyoshi et al (2017) showed that use of layer stacking from time-series images improved classification, and they achieved an 18% increase in kappa coefficient. Recent studies have used all available cloud-free satellite scenes during a year to classify tree species.…”
Section: Assessment Of Classification Accuracymentioning
confidence: 99%
“…Hill et al (2010) had reported that the ability to discriminate and map temperate deciduous tree species in airborne multispectral imagery increased using timeseries data: from kappa 0.67 for a single image to kappa 0.85 for three images combined (one from autumn, one from the green-up, and one from full-leaf phase). Miyoshi et al (2017) showed that use of layer stacking from time-series images improved classification, and they achieved an 18% increase in kappa coefficient. Recent studies have used all available cloud-free satellite scenes during a year to classify tree species.…”
Section: Assessment Of Classification Accuracymentioning
confidence: 99%
“…Consequently, to detect small differences in the spectral signatures of species, instruments with many contiguous bands at small bandwidths (<20 nm) tend to produce better classification accuracy [13]. The most important regions of the electromagnetic spectrum for distinguishing plant species are the near infra-red (NIR) and short-wave infrared (SWIR) regions [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…One way to enhance the spectral differences between species is to utilize multiple images, taken across a growing season [22,33]. Studies have shown that, when using a single image to map plant species, an image that is taken at peak productivity often produces the most accurate results [20,30,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a growing number of studies have taken advantage of UAVs to obtain information on seasonal changes for different tree species in order to understand their distributions. Lisein et al [16] and Miyoshi et al [17] found that phenological information can improve the classification results of tree species classification. They also state that the information acquired in leaf transition states makes the most significant contribution.…”
Section: Introductionmentioning
confidence: 99%